Brand Revitalization. (November 2014) - Dev, Chekitan S.; Keller, Kevin Lane
In this essay, we discuss brand revitalization in the context of a revitalization process undertaken by of one of India's iconic hotel brands: The Park Hotels. The leadership team of The Park Hotels, in collaboration with well-known brand-consulting firm Landor, undertook a two-year process to revitalize an already well-established brand in the face of severe competitive threat and changing customer tastes. This article presents a seven-step process for The Park's brand revitalization effort, which begins with strategy and ends with implementation. The seven steps are (1) conduct a comprehensive brand audit, (2) determine the brand position, (3) develop the brand platform, (4) establish the brand beliefs, (5) evoke the brand experience, (6) develop the brand voice, and (7) launch the new brand. This essay, the first ever to lift the veil on a proprietary hospitality branding project, depicts how The Park addressed its particular strategic approach of tying together a set of distinctive boutique hotels with a unifying and inspiring brand position.